OPTIMALISASI TARGET HAFALAN AL-QUR'AN MELALUI MANAJEMEN DIRI DAN PENGELOLAAN PROGRAM TAHFIDZ UNTUK KESEJAHTERAAN PSIKOLOGIS SANTRI - Shofi Aqidatul Izzah; Siti Norsaniyah; Jazilurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Optimizing Qur'anic memorization targets requires effective self-management, well-organized tahfidz program management, and positive psychological well-being. This study aims to examine how self-management and tahfidz program management optimize Qur'anic memorization targets and promote the psychological well-being of students at PPIQ Al-Hasyimiyah, Nurul Jadid Islamic Boarding School, Paiton, Probolinggo. This study employed a qualitative case study approach. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model. Data trustworthiness was ensured through source and technique triangulation. The findings indicate that the optimization of Qur'anic memorization targets is supported by three interrelated aspects: self-management, including time management, priority setting, self-evaluation, consistent muraja'ah, self-control, and learning motivation; tahfidz program management through musyrifah supervision, memorization evaluation, and structured scheduling; and psychological well-being, reflected in self-acceptance, self-confidence, learning motivation, positive social relationships, stress management, and satisfaction with memorization progress. The study proposes a conceptual model demonstrating that the synergy between students' self-management, effective tahfidz program management, and positive psychological well-being contributes to optimizing Qur'anic memorization targets.